Hubungan Partisipasi Kader dalam Pelaksanaan Desa Siaga terhadap Pelayanan Kia Di Desa Karanganyar Kabupaten Cirebon Tahun 2020 - Atiek Novianty (Syntax Corporation Indonesia, 2021)
AKI and AKB are still a concern for each country and a top priority for improving the health of mothers, newborns. By improving health services, especially maternal and child health, and efforts to develop Desa Siaga can involve the community and cadre participation. A cadre is a community chosen, can guide the community in health issues independently, help health workers in an effort to improve health status. The purpose of the study was to determine the relationship between Kader participation and the delivery of Mataernal and Neonatal services. This study uses an observational analytic research design with a cross sectional approach using primary data from questionnaire sheets and village standby indicator checklist. The population and sample in the study were all health cadres in Karanganyar Village with 27 respondents. This research was conducted in February-March 2020. Data analysis in this study used Univariate analysis in the form of frequency tables and Bivariate analysis using Chi Square Test. The results showed that 27 samples of 13 (48.1) respondents had a sufficient level of participation in providing Mataernal and Neonatal services, 4 (14.8) respondents with a less level of participation were not given Mataernal and Neonatal services, and 2 (3.7) respondents with a level of participation. well, the provision Mataernal and Neonatal services is not carried out. After doing the Chi Square test, the p value is 0.135, which means p> 0.05 with a positive correlation value of 0.103, which means that the closeness of the relationship is very low.0020The conclusion of this study is that there is no relationship between cadre participation and the provision of Mataernal and Neonatal services services in Karanganyar Village, the Kubangdeleg Community Health Center in 2020. It is hoped that each cadre can play an active role in carrying out tasks in health services, especially in KIA services, capable of empowering and mobilizing communities in village implementation